JDP2 overexpression provokes cardiac dysfunction in mice - Heger, Jacqueline; Bornbaum, Julia; Würfel, Alona; Hill, Christian; Brockmann, Nils; Gaspar, Renata; Paloczi, Janos; Varga, Zoltan V.; Sarközy, Marta; Bencsik, Peter; Csont, Tamás; Török, Szilvia; et al. (My University, 2018)
The transcriptional regulator JDP2 (Jun dimerization protein 2) has been identified as a prognostic marker for patients to develop heart failure after myocardial infarction. We now performed in vivo studies on JDP2-overexpressing mice, to clarify the impact of JDP2 on heart failure progression. Therefore, during birth up to the age of 4 weeks cardiac-specific JDP2 overexpression was prevented by doxycycline feeding in transgenic mice. Then, JDP2 overexpression was started. Already after 1 week, cardiac function, determined by echocardiography, decreased which was also resembled on the cardiomyocyte level. After 5 weeks blood pressure declined, ejection fraction and cardiac output was reduced and left ventricular dilatation developed. Heart weight/body weight, and mRNA expression of ANP, inflammatory marker genes, collagen and fibronectin increased. Collagen 1 protein expression increased, and fibrosis developed. As an additional sign of elevated extracellular matrix remodeling, matrix metalloproteinase 2 activity increased in JDP2 mice. Thus, JDP2 overexpression is deleterious to heart function in vivo. It can be concluded that JDP2 overexpression provokes cardiac dysfunction in adult mice that is accompanied by hypertrophy and fibrosis. Thus, induction of JDP2 is a maladaptive response contributing to heart failure development.
Keywords: ddc:150